2021
DOI: 10.3389/fgene.2021.664717
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated With Pre- and Perinatal Exposure to Arsenic

Abstract: Inorganic arsenic is a well-established human carcinogen, able to induce genetic and epigenetic alterations. More than 200 million people worldwide are exposed to arsenic concentrations in drinking water exceeding the recommended WHO threshold (10μg/l). Additionally, chronic exposure to levels below this threshold is known to result in long-term health effects in humans. The arsenic-related health effects in humans are associated with its biotransformation process, whereby the resulting metabolites can induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…Accumulated evidence indicates that prenatal and early life arsenic exposure can cause a variety of detrimental health effects during childhood and increase the risk of developing diseases such as bladder, lung, kidney, and liver cancer in adulthood [2] . Our previous findings provide supportive evidence that arsenic exposure in utero was associated with various types of genetic damage in the newborn that may potentially contribute to increased risk of cancer development later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence indicates that prenatal and early life arsenic exposure can cause a variety of detrimental health effects during childhood and increase the risk of developing diseases such as bladder, lung, kidney, and liver cancer in adulthood [2] . Our previous findings provide supportive evidence that arsenic exposure in utero was associated with various types of genetic damage in the newborn that may potentially contribute to increased risk of cancer development later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence revealed that arsenic is a transplacental carcinogen [1] . Arsenic exposure can cause detrimental health effects, particularly during pregnancy, which is a sensitive period for the developing fetus [2] . In utero arsenic exposure is associated with various types of genetic damage in the newborn such as 8-hydroxydeoxyguanine (8-OHdG), 8-nitroguanine, and micronuclei, which may contribute to the development of a variety of diseases including cancer later in life [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…85 Accumulating evidence strongly suggests that early life exposure to arsenic increases susceptibility to disease. 86 Arsenic transport pathways: Involvement in toxicity and detoxification. Several comprehensive reviews on cellular uptake and efflux pathways for arsenic are available.…”
Section: Arsenicmentioning
confidence: 99%
“…In addition to cancer, chronic arsenic exposure is associated with a myriad of other adverse health effects, including cardiovascular, respiratory, and neurological diseases, skin disorders, and diabetes 85 . Accumulating evidence strongly suggests that early life exposure to arsenic increases susceptibility to disease 86 …”
Section: Emerging Topics In Toxicity: Metals and Metalloids Of Enviro...mentioning
confidence: 99%
“…Ranked at the top of the United States Agency for Toxic Substances and Disease Registry (ATSDR)’s priority list of Hazardous Substances, arsenic is a Group 1 (proven) human carcinogen. Chronic exposure is associated with higher chances of a number of diseases [ 1 , 2 , 3 ]. Currently, the maximum contaminant level (MCL) for arsenic in drinking water set by the United States Environmental Protection Agency (EPA) is 10 ppb (parts per billion), a standard accepted by most other countries.…”
Section: Introductionmentioning
confidence: 99%